1992
DOI: 10.1002/pros.2990210206
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of epidermal growth factor and transforming growth factor beta in human prostatic epithelial cells in culture

Abstract: The present study was conducted to study the interaction between epidermal growth factor (EGF) and transforming growth factor-beta (TGF-beta) in benign human prostatic epithelial cells in culture. Primary cultures of human prostatic epithelial cells were grown in complete WAJC, which consisted of WAJC-404 medium and, in addition to other defined additives, EGF and bovine pituitary extract (BPE). Incomplete WAJC contained the same composition except EGF and BPE were deleted. TGF-beta was added into media at con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 8 publications
1
37
0
3
Order By: Relevance
“…TGF-b1 is a pluralistic factor that can inhibit proliferation, induce apoptosis, promote angiogenesis and suppress immunity, all of which can enhance tumour development, progression and invasiveness. [41][42][43][44][45][46] Therefore, our findings indicate TGF-b1 as another possible factor involved in zonal differences. IGF-1 stimulates cell proliferation and inhibits apoptosis [47][48][49][50] and has also been reported as a potent angiogenic factor.…”
Section: Differential Effects Of Pzsc and Tzsc On Pc3 Cellsmentioning
confidence: 54%
“…TGF-b1 is a pluralistic factor that can inhibit proliferation, induce apoptosis, promote angiogenesis and suppress immunity, all of which can enhance tumour development, progression and invasiveness. [41][42][43][44][45][46] Therefore, our findings indicate TGF-b1 as another possible factor involved in zonal differences. IGF-1 stimulates cell proliferation and inhibits apoptosis [47][48][49][50] and has also been reported as a potent angiogenic factor.…”
Section: Differential Effects Of Pzsc and Tzsc On Pc3 Cellsmentioning
confidence: 54%
“…Nevertheless, in primary cultures of normal prostatic epithelial cells, TGFb typically induces growth arrest and other phenotypic changes, but not apoptosis (Peehl et al 1994b). However, Sutkowski et al (1992) reported that TGFb induced apoptosis in primary cultures if the potent mitogen and survival factor, EGF, was deleted from the culture medium. This finding suggests that the activity of TGFb and/or the ability to undergo apoptosis in general depends on the local milieu of growth and survival factors.…”
Section: Apoptosismentioning
confidence: 99%
“…Receptors for TGF 1 have also been identified in the human prostate cancer cell lines DU145 and PC-3 (Wilding et al 1989). TGF 1 has a mainly inhibitory effect on human prostatic fibroblasts and epithelial cells in culture (Sutkowski et al 1992, Story et al 1993. Our studies have confirmed this mainly inhibitory effect, which was most marked in cultures which contained low levels of FGF2.…”
Section: Figurementioning
confidence: 99%
“…TGF 1 and TGF 2 have been identified in human prostate and implicated in prostatic disease (Knabbe et al 1993, Truong et al 1993. Addition of TGF 1 to cultured prostatic epithelial and stromal cells has been reported to inhibit proliferation in both cell types (Sutkowski et al 1992). However, low levels of TGF 1 have been shown to result in small increases (1·5-fold) in cell proliferation in both stroma and epithelium (Collins et al 1996).…”
Section: Introductionmentioning
confidence: 99%